Automated Job Design: Balancing Technological Efficiency and Human Role Effectiveness in Indonesia's Maritime Sector - Dewa Putu Yohanes Agata L. Sandopart (Varied Knowledge Journal, 2025)
This study investigates the challenges of job design within the context of maritime sector automation, focusing specifically on the preferences of the Generation Z workforce. Employing a case study approach across three Indonesian maritime entities alongside a comparative international literature review, this research identifies a fundamental tension between the demands of technological efficiency and the necessity for human role effectiveness. The principal findings indicate that Generation Z in the maritime sector exhibits a strong preference for RAISA (Robotics, Artificial Intelligence, and Service Automation) technologies as assistive tools rather than as replacements. The highest acceptance rate was recorded for decision-support systems (86.4%), while the lowest was for fully automated customer interaction (23.7%). This study proposes a novel Hybrid Role Integration (HRI) model that synthesizes the principles of technical efficiency with the psychological meaningfulness of work. The research's novelty lies in integrating the digital native generation's perspective into the maritime job design framework, alongside the development of human role effectiveness indicators specific to the operational context of archipelagic waters. Practical implications encompass policy recommendations for human-machine collaboration training and the restructuring of career pathways based on hybrid competencies.